School leadership: Results from a case study at a teacher training school in Benguela province - Abelha, Marta (2017)
In the present study, the research problem lies in school leaders’ context, particularly in how teachers at a teacher´s training school in Benguela province perceives the leadership of the school principal. To answer the research problem were defined three objectives: i) characterize how teachers of the training school for teachers in Benguela province perceive the leadership led by the school principal; ii) understand the influence of the school principal in the teaching work dynamics iii) develop knowledge about the style of leadership developed in the training school for teachers in Benguela province. The adopted research methodology assumed predominantly a qualitative nature, and case study was the chosen research strategy. The empirical study took place in the academic year 2014 in a teacher training school in Benguela province. The main data collection technique was the MLQ questionnaire of Avolio & Bass (2004) applied to all the teachers (n=20). A simple statistical analysis was the privileged data processing technique. The school principal of the teacher´s training school in Benguela province reveal behavioral attitudes and positions in line with the Laissez-Faire Leadership and some categories of Transformational Leadership were the main results of this study.